Two fast prototypes of web-based augmented reality enhancement for books. Issue 10 (2nd December 2019) - Lou, Dan
Abstract : Purpose: The purpose of this paper is to identify a light and scalable augmented reality (AR) solution to enhance library collections. Design/methodology/approach: The author first did research to identify the major obstacle in creating a scalable AR solution. Next, she explored possible workaround methods and successfully developed two prototypes that make the current Web-based AR work with ISBN barcode. Findings: Libraries have adopted AR technology in recent years mainly by developing mobile applications for specific education or navigation programs. Yet a straight-forward AR solution to enhance a library's collection has not been seen. One of the obstacles lies in finding a scalable and painless solution to associate special AR objects with physical books. At title level, books already have their unique identifier – the ISBN number. Unfortunately, marker-based AR technology only accept two-dimensional (2-D) objects, not the one-dimensional (1-D) EAN barcode (or ISBN barcode) used by books, as markers for technical reasons. In this paper, the author shares her development of two prototypes to make the Web-based AR work with the ISBN barcode. With the prototypes, a user can simply scan the ISBN barcode on a book to retrieve related AR content. Research limitations/implications: This paper mainly researched and experimented with Web-based AR technologies in the attempt to identify a solution that is as platform-neutral as possible, and as user-friendly as possible. Practical implications: The light and platform-neutral AR prototypes discussed in this paper have the benefits of minimum cost on both the development side and the experience side. A library does not need to put any additional marker on any book to implement the AR. A user does not need to install any additional applications in his/her smartphone to experience the AR. The prototypes show a promising future where physical collections inside libraries can become more interactive and attractive by blurring the line of reality and virtuality. Social implications: The paper can help initiate the discussion on applying Web-based AR technologies to library collections.